Ameliorative effect of lycopene effect on cisplatin-induced nephropathy in patient - Leila Mahmoodnia; Keivan Mohammadi; Rohollah Masumi (Society of Diabetic Nephropathy Prevention, 2017)
Background: Nephrotoxicity is one of the most important limitations of cisplatin-based chemotherapies which associated with many complications and high mortality rate. Objectives: To investigate the effect of lycopene on cisplatin-induced nephrotoxicity in patients with cancer. Patients and Methods: In this double-blind, randomized clinical trial, 120 patients were randomly assigned to two groups, case (treated with lycopene + standard regimen of kidney injury prevention) and control (treated with only the standard regimen of kidney injury prevention). Lycopene was orally taken from 24 hours before to 72 hours after cisplatin administration. Blood urea nitrogen (BUN), serum creatinine (Cr), and glomerular filtration rate (GFR) were measured and recorded. The data were analyzed using SPSS. Results: Changes in Cr were not significantly different between the two groups (P = 0.131). However, a significant decreasing trend was seen in GFR during the study, which was more marked in the control group (P = 0.004). BUN significantly decreased during the study (P = 0.002), and a significant decrease of BUN on the day three in both groups was seen (P = 0.001). However, BUN increased in the case group on the day 21 of treatment. The corresponding increase was less marked in the control group. Conclusions: Lycopene can be considered a useful adjuvant therapy to decrease the complications due to cisplatin-induced nephrotoxicity in patients with cancer.